2006
DOI: 10.1080/09603100500386206
|View full text |Cite
|
Sign up to set email alerts
|

09/11 on the USD/EUR foreign exchange market

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…However, if dealers can't provide the liquidity as required, it will cause trouble such as ruined reputations; in this case, dealers have to be reliable. For example, the FX market continued uninterruptedly and functioned successfully even in the events of September 11, 2001 [34]. However, the traditional customer market is fairly decentralized and opaque.…”
Section: Customer Marketmentioning
confidence: 99%
“…However, if dealers can't provide the liquidity as required, it will cause trouble such as ruined reputations; in this case, dealers have to be reliable. For example, the FX market continued uninterruptedly and functioned successfully even in the events of September 11, 2001 [34]. However, the traditional customer market is fairly decentralized and opaque.…”
Section: Customer Marketmentioning
confidence: 99%
“…This also proved true in a similar analysis of US equities by Choudhry (2005) who used daily data and identified a rise in the systematic risk of transportation, recreation and aerospace firms following 9-11. Mende (2006) used minute-by-minute data from the USD/EUR foreign exchange market around the time of the 9-11 attacks to examine market efficiency. This showed that spreads and volatility increased sharply after the attacks, but returned to normal within a few hours.…”
Section: September 11 Terrorist Attacksmentioning
confidence: 99%
“…Results show that for the Dow Jones Euro STOXX 50 (FESX) and the DAX future (FDAX), there is a clear decrease in the average holding period in the 9 days after the 09/11 terrorist attacks. Mende (2006) studies the effect of 09/11 on the relationship between trading volume and volatility in the USD/EUR foreign exchange market. This relationship depends on the market size, its degree of liquidity, and the flow of information reaching the market (Karpoff, 1987).…”
Section: The Impact Of Information Shocks On Financial Marketsmentioning
confidence: 99%
“…In contrast, Chen and Siems (2004) and Mende (2006) show that there is an increased market resilience and an efficient processing of terrorist attacks in financial markets of developed countries. This raises the question of whether the identified structural shift was triggered by the events of 09/11 or was coincidental with the stabilization of the relationship between LIFFE and Eurex.…”
mentioning
confidence: 92%